Financial Sector Assessment Program Update : Trinidad and Tobago Credit Unions - Rutman, Jose (World Bank, Washington, DC, 2021)
The Credit Union (CU) sector is concentrated and has a significant number (129) of institutions. CU sector’s loan portfolio is concentrated mainly in consumer loans. The prudential and market conduct situation of the CU sector present weaknesses. The legal framework for CUs is outdated (from 1971) and has significant limitations for an appropriate prudential regulation and supervision of the sector. A new legal framework for the regulation and supervision of CUs should be developed urgently.